Das neue Bild von den atmosphärischen Fronten - Kraus, Helmut (ERDKUNDE, 1995)
Fronts play a major role in meteorology. This is true for synoptic-scale fronts as frequent weather phenomena as well as for small-scale fronts, e. g. sea-breeze fronts. However, for many scientists and practitioners understanding of these phenomena is still connected with the air-mass theory of the early twenties of this century. But together with the enormous progress in meteorology conceptual thinking concerning this topic has changed drastically, and a new view of atmospheric fronts has developed. This article tries to elucidate this new look avoiding complex mathematical formalisms. In doing so, emphasis is laid on: (a) the definition of a front as a three-dimensional domain, in which the gradient of any atmospheric characteristic (in most cases the temperature gradient) possesses large values compared with those in the environment; (b) the processes of cross-front circulation (being responsible for precipitation) and frontogenesis, which are closely related to each other; (c) the along-front jet; (d) the coupling of frontogenesis and cyclogenesis; (e) the large variety of the frontal structures and of the frontal forcing, both are responsible for the large variety of the weather connected with fronts. Fronts always belong to atmospheric motion systems of a larger (than the frontal) scale; they are structure elements or simply parts of their parent motion system. In this sense this article deals mainly with synoptic-scale fronts belonging to mid-latitude cyclones. But in addition, it will also consider fronts, which are parts of meso- or micro-scale motion systems.